2011
DOI: 10.1111/j.1468-5906.2010.01559.x
|View full text |Cite
|
Sign up to set email alerts
|

Changing Patterns of Attendance at Religious Services in Canada, 1986-2008

Abstract: According to the General Social Survey, the combined rate of weekly and monthly attendance at religious services in Canada has declined by about 20 points from 1986 to 2008. Approximately half of this decline stems from the increase in the proportion of people reporting no religion, who, for the most part, do not attend religious services. The other portion of this decline is attributable to eroding attendance rates among Catholics, particularly older Catholics, and Protestants in Québec. Attendance rates for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 17 publications
(17 reference statements)
4
47
0
Order By: Relevance
“…Eagle (2011:192) maintains that the Project Canada samples have included “an inordinate number of Protestants”—a strong statement given how closely the PCS figures match the census figures. He could be right.…”
Section: The Quality Of the Project Canada Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Eagle (2011:192) maintains that the Project Canada samples have included “an inordinate number of Protestants”—a strong statement given how closely the PCS figures match the census figures. He could be right.…”
Section: The Quality Of the Project Canada Samplesmentioning
confidence: 99%
“…In his Journal for the Scientific Study of Religion article earlier this year, David Eagle (2011) provided an important contribution to an understanding of religion in Canada by examining attendance patterns since the mid‐1980s. Such clarification is valuable not only to those who are studying religion in Canada, but to those who see Canada as something of a case study that potentially offers insights into religious developments in other settings, including the United States and Europe.…”
mentioning
confidence: 99%
“…Using 1985 to 2004 Canadian General Social Survey (CGSS) data, Clark and Schellenberg (2006) found that the percentage of weekly attenders declined from 41 to 31 percent and non-attenders increased from 31 to 43 percent. Eagle (2011) While each of these studies focuses primarily on Canada, others put Canadian attendance in a cross-cultural context. Reimer (1995) compared Canadian and American attendance using the 1983 WVS, 1988 AGSS, and 1990 PCS data sets.…”
Section: Analysis Of Trendsmentioning
confidence: 99%
“…They leave traditional forms of the church, but have not left behind their faith and the church as such. 9 The ambivalent middle refers to people who are neither religiously active nor opposed to religious involvement. They are people interested in spirituality, but not necessarily church.…”
Section: Emerging Christians and The Decline Of Evangelical Church Atmentioning
confidence: 99%
“…They all agree that religious participation among Canadians is in decline and the only categories that show any meaningful growth are non-attendance and no religious affiliation. See [7][8][9][10][11]. 7 Eagle believes this transition reflects the process of secularization.…”
Section: Emerging Christians and The Decline Of Evangelical Church Atmentioning
confidence: 99%